1981
DOI: 10.1515/jpme.1981.9.3.124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of terbutaline on the fetal lamb during maternal oxytocin-induced uterine contractions

Abstract: Terbutaline, a resorcinol derivative of isoprenaline, is primarily an adrenergic j3 2 -receptor agonist [25]. Terbutaline has been demonstrated äs being a potent inhibitor of myometrial contractlity in vitro [1]. Recent clinical trialshave confirmed the agent's tocolytic activity in both spontaneous and oxytocin-stimulated labor [2,3,15]. the investigations showed that terbutaline was well tolerated maternally despite a moderate tachycardia. Antepartum fetal heart rate monitoring and APGAR scores did not demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1987
1987

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In several studies [1,9,11] increases in uterine blood flow were reported while other studies [2,3,4,6,7,8,10,12] showed no changes or even decreases in flow after betaadrenergic drug infusion. Part of these differences might be explained by the fact that different betasympathomimetic drugs were used, but more important seems the site of flow measurement in the pelvic vascular bed.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies [1,9,11] increases in uterine blood flow were reported while other studies [2,3,4,6,7,8,10,12] showed no changes or even decreases in flow after betaadrenergic drug infusion. Part of these differences might be explained by the fact that different betasympathomimetic drugs were used, but more important seems the site of flow measurement in the pelvic vascular bed.…”
Section: Introductionmentioning
confidence: 99%